Change of contraceptive preference after the free-LARC program for Thai teenagers - Sathaphone Inthavong; Tawiwan Pantasri; Nuntana Morakote; Tanarat Muangmool; Wirawit Piyamongkol; Saipin Pongsatha; Somsak Chaovisitseree (BMC, 2022)
Abstract Background In 2014, the Thai government launched a free-of-charge long-acting reversible contraception (LARC) program for Thai female adolescents. However, its acceptance had not been reported. Therefore, this study aimed to describe contraceptive use among women of reproductive age before and after the program was implemented. Methods This retrospective cross-sectional study was carried out from the medical records of 9000 women of reproductive age, who attended the Family Planning Clinic at Maharaj Nakorn Chiang Mai Hospital between 2009 and 2018. The Chi-square test was used to compare the contraceptive methods administered before and after the program was implemented, and binary logistic regression was used to find the factors associated with implant use after completion of the program. Results Depot medroxy progesterone acetate (DMPA) injection was the most popular contraceptive method used among 40.9% of the women. The rates of subdermal implant use were increased significantly after the program was implemented (2.3-9.3%, p < 0.001). Implant use for adolescents aged less than 20 years increased from 2.6% to 56.4%, while DMPA was the most popular method used among adult women at 36.4%. Factors associated significantly with implant use after implement of the program included age of less than 20 years (aOR = 4.17 (CI: 1.84-9.44); p = 0.001) and nulliparity (aOR = 8.55 (CI: 3.77-19.39); p < 0.001). Conclusion This study showed a significant increase in contraceptive implant use after the free-LARC program for adolescents had been applied. Statement of implications Contraceptive implant is the most effective hormonal reversible contraception. Its use rate is low among all age groups, but increased clearly after the free-of-charge program was applied for adolescents.